Exploring Customer Loyalty Drivers in Indonesian Islamic Bank After Cybersecurity Breaches Using SEM Approach - Mia Sari; Indra Indra; Ririn Riani (Journal of Islamic Monetary Economics and Finance, 2025)
This study explores the factors influencing customer loyalty at Bank Syariah Indonesia (BSI) after cyberattacks, using the Expectation Confirmation Theory (ECT) as the theoretical framework. A quantitative approach with Partial Least Squares-Structural Equation Modeling (PLS-SEM) is applied, analyzing data from 225 customers affected by service disruptions, ATM use, and Mobile Banking. The findings indicate that customer loyalty is significantly affected by service quality, religiosity, and customer trust. Furthermore, customer trust after a cyberattack is significantly influenced by service quality and religiosity. The Compliance, Assurance, Reliability, Tangibles, Empathy, and Responsiveness (CARTER) model is used to measure service quality, emphasizing both technical and ethical aspects. The results highlight the importance of successful crisis management, clear communication, improved security, and compensating customers in retaining and potentially growing the customer base post-attack. This research underscores the significance of the CARTER model in evaluating service quality and the role of religiosity in fostering customer loyalty. The study emphasizes that Islamic banks should integrate technical and ethical aspects of service to minimize negative impacts and maintain customer loyalty.